HUBUNGAN GERAKAN WUDHU DAN GERAKAN SHOLAT TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 5–6 TAHUN DI TAMAN KANAK-KANAK ISLAM KHAIRUNNISA KOTA JAMBI - Azzahra, Nazila Rizky; Shalahuddin; Jamilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gross motor skills involve the coordination of large muscle movements that emphasize physical strength, balance, and body control in early childhood. Body movement activities serve as effective stimulation to optimize children’s physical development. This study aims to determine the relationship between ablution (wudhu) movements and prayer (shalat) movements on the gross motor development of children aged 5–6 years at Khairunnisa Islamic Kindergarten, Jambi City. The research employed a quantitative correlational approach using the product-moment formula. The sampling technique applied was random sampling, involving 30 children for pilot testing and 52 children as the main research sample. Data were collected through questionnaires and documentation, and analyzed using multiple linear regression with SPSS version 25. The findings reveal a positive and significant relationship between ablution movements and prayer movements simultaneously on children’s gross motor development. The significance value for ablution movements was 0.023 and for prayer movements was 0.009, both indicating statistical significance. These results suggest that structured religious movement activities such as wudhu and shalat can contribute effectively to the improvement of gross motor skills in early childhood education. Therefore, integrating religious physical practices into daily learning activities may support both motor development and spiritual formation of young children.